2022
DOI: 10.1007/s11523-021-00859-6
|View full text |Cite
|
Sign up to set email alerts
|

A Phase IIIb Open-Label, Single-Arm Study of Afatinib in EGFR TKI-Naïve Patients with EGFRm+ NSCLC: Final Analysis, with a Focus on Patients Enrolled at Sites in China

Abstract: Background Afatinib has been shown as a suitable option for the treatment of epidermal growth factor receptor mutationpositive (EGFRm+) non-small-cell lung cancer (NSCLC) in randomized controlled trials. However, patients treated in realworld clinical practice, including elderly patients, and those with brain metastases or poor Eastern Cooperative Oncology Group (ECOG) performance statuses, are often excluded from these studies. Objective To report the final results, with a particular focus on patients enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In a randomized phase II study (LUX-Lung 7), Afatinib showed superior outcomes compared to Gefitinib in advanced NSCLCm+ patients (PFS: 11.0 months vs 10.9 months, HR: 0.73, 95% CI: 0.57-0.95, p = 0.017; ORR: 70% vs 56%, odds ratio (OR): 1.87, 95% CI: 1.18-2.99, p = 0.00083) 18 . A single-arm phase III study conducted in China further confirmed the feasibility of Afatinib as a therapy for Chinese patients with advanced NSCLCm+ (ORR: 59.1%, PFS: 11.4 months) and did not reveal any new safety concerns 19 . Consequently, Afatinib as a neoadjuvant treatment might offer advantages over first-generation EGFR-TKIs for locally advanced NSCLCm+.…”
mentioning
confidence: 77%
“…In a randomized phase II study (LUX-Lung 7), Afatinib showed superior outcomes compared to Gefitinib in advanced NSCLCm+ patients (PFS: 11.0 months vs 10.9 months, HR: 0.73, 95% CI: 0.57-0.95, p = 0.017; ORR: 70% vs 56%, odds ratio (OR): 1.87, 95% CI: 1.18-2.99, p = 0.00083) 18 . A single-arm phase III study conducted in China further confirmed the feasibility of Afatinib as a therapy for Chinese patients with advanced NSCLCm+ (ORR: 59.1%, PFS: 11.4 months) and did not reveal any new safety concerns 19 . Consequently, Afatinib as a neoadjuvant treatment might offer advantages over first-generation EGFR-TKIs for locally advanced NSCLCm+.…”
mentioning
confidence: 77%
“…The exon 20 point mutation pS768I showed a good response to afatinib (a median PFS of 14.7 months) in the trials LUX-lung 2, 3 and 6 [14], and a PFS of 12.3 months in patients treated with osimertinib in a recent trial [61]. One real-world study with afatinib focusing on Chinese patients showed a prevalence of 12% of uncommon mutations; the entire patient population harboring uncommon mutations had a PFS of 9.06 months [64]. A recent large study on a database of 693 EGFR mutant patients harboring 98 different uncommon mutations explored the efficacy of afatinib; the data have been collected from randomized clinical trials and phase IIIb trials, compassionate-use/expanded-access programs, noninterventional trials, case series or case studies [65,66].…”
Section: Treatment Activity Data Of Different Tkismentioning
confidence: 99%